UPAYA MENINGKATKAN KEMAMPUAN BERBAHASA ANAK MELALUI METODE BERCERITA DI TK MIFTAHUL KHAIR - Hamsiani Hamsiani; Syamsul Alam Ramli (Jurnal Panrita, 2020)
This research is a classroom action research which examines 13 children of TK Miftahul Khair in Limbong Village in the academic year 2020/2021 related to children's language learning through storytelling methods. The goal to be achieved is to improve children's language skills in composing sentences through the storytelling method. The method used is classroom action research with data collection using observation sheets. The collected data were analyzed using quantitative descriptive statistics. So based on the results of the overall study of 13 children, the results of children's language skills in cycle I were 63% and cycle II was 84%, so there was an increase of 21%. Based on the results of this study, it can be concluded that the storytelling method can improve children's language skills.